Una poética crítica: Libro y lectura en el Perú - Cortéz, Enrique (2005)
The concern for the book always implies a question for reading; the question of reading does not necessarily imply the presence of the book. This, which seems like a play on words, makes sense: it is presented as a general observation of a not very happy relationship between books and reading, in a context such as Peru; thus, it updates a tension plotted throughout its history, under various modalities.